Katolicka doktryna o sposobie obecności Chrystusa w postaciach eucharystycznych wyrażona w mszale dla byłych anglikanów - Beyga, Paweł (Poznańskie Studia Teologiczne, 2020)
The ecumenical dialogue between the Catholic Church and the Anglican Communion is one of the most important and difficult part of activity of both communities. Eucharist is the main goal of ecumenism because in the common celebrating of the sacred liturgy the Christ’s Church is a visible sign of the unity for the world. One of the most important theological problems in the dialogue is the problem of transsubstantiation. For the Anglican Church this Catholic doctrine is against the biblical and rudimental teaching of primitive Christendom. The article shows the problem of trans- substantiation in the ecumenical perspective and in the context of Divine Worship: The Missal. The Catholic Eucharistic teaching is present in this new Western liturgical book, but the term of trans- substantiation does not exist there.